Microbial involvement in iodine cycle: mechanisms and potential applications - Duborská, Eva; Vojtková, Hana; Matulová, Michaela; Šeda, Martin; Matúš, Peter (Frontiers in Bioengineering and Biotechnology, 2023)
Stable iodine isotopes are essential for humans as they are necessary for producing thyroid gland hormones. However, there are hazardous radioactive iodine isotopes that are emitted into the environment through radioactive waste generated by nuclear power plants, nuclear weapon tests, and medical practice. Due to the biophilic character of iodine radionuclides and their enormous biomagnification potential, their elimination from contaminated environments is essential to prevent the spread of radioactive pollution in ecosystems. Since microorganisms play a vital role in controlling iodine cycling and fate in the environment, they also can be efficiently utilized in solving the issue of contamination spread. Thus, this paper summarizes all known on microbial processes that are involved in iodine transformation to highlight their prospects in remediation of the sites contaminated with radioactive iodine isotopes.